Distribution of trace elements in the tissues of benthic and pelagic fish from the Kerguelen Islands - Bustamante, Paco; Bocher, Pierrick; Cherel, Yves; Miramand, Pierre; Caurant, Florence (Science of The Total Environment, 2003)
International audience New information on the concentrations of Cd, Cu, Hg and Zn in the liver, kidney and muscles of eight marine benthic and pelagic sub-Antarctic previous termfishnext term species are presented to determine the importance of these metals in the marine systems of the Kerguelen Islands. Compared to the reported metal concentrations in other Antarctic previous termfishnext term species, the present results are globally within the same range of concentrations, although Cd displayed a very high interspecific variability in liver and kidney. Indeed, the highest Cd concentrations in liver, ranging from 10.0 to 52.1 μg g−1 dry wt. but also the lowest Cd concentrations in muscles (<0.030 μg g−1 dry wt.) have been displayed by the pelagic Myctophidae Gymnoscopelus piabilis. Metal concentrations differences might be related to diet and feeding habits of benthic and pelagic previous termfishnext term species. However, Cd and Hg concentrations in the edible muscle are lower than the French limit values (less-than-or-equals, slant0.155 μg Cd g−1 dry wt. and less-than-or-equals, slant1.51 μg Hg g−1 dry wt.) for these toxic metals as well as for edible and non-commercially interesting previous termfishnext term species. Results for Cd in previous termfishnext term tissues are consistent with the hypothesis of Cd-enrichment in the polar food webs typically explained by essential elements depletion. In fact, Zn concentrations in previous termfishnext term from the Kerguelen Islands are comparable to those of other areas but low Cu concentrations in previous termfishnext term livers, ranging from 0.9 to 24.7 μg g−1 dry wt., might indicate low availability of this essential element in these sub-Antarctic waters.